Perancangan produk pet furniture untuk home office dengan pendekatan sustainable design - Saputri, Hayu Puspasari; Kusumarini, Yusita; Kayogi, David Tan (Institut Seni Indonesia Yogyakarta, 2025)
Human beings are the social species that relies on social interaction to survive and thrive. The COVID-19 pandemic hinders this process and made the basic human social needs was put on halt. When these needs cannot be met, humans will use alternative social inputs sources, one of which is through the adoptions of pets. The COVID-19 pandemic is the biggest factor in pet adoption in 2020 (Morgan L, et al. 155). The increase of pet adoption was caused by the increasing feeling of loneliness due to governments restrictions on social activities. The COVID-19 also causes the rise of remote working activities around the world. Interior Design prioritizes human relationships in a space which is an important factor in making a design that could provide a deeper connection for the users. In a workspace, productivity was supported by comfort, especially when working from home. The designing process uses Design Thinking method to produce the appropriate design for the users. The need for integrated pet furniture and human furniture deepens each year, thus the demand for integrated design was prevalent. To create comfortable working situation for pets and human the research was conducted to produce the furniture that could fulfil the need. The results of this study are to produce four different furniture product set that would benefits the user and their respective pets.